2020
DOI: 10.1002/mnfr.202000068
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Chicory Fructo‐Oligosaccharides and Native Inulin by Infant Fecal Microbiota Attenuates Pro‐Inflammatory Responses in Immature Dendritic Cells in an Infant‐Age‐Dependent and Fructan‐Specific Way

Abstract: Scope Inulin‐type fructans are commonly applied in infant formula to support development of gut microbiota and immunity. These inulin‐type fructans are considered to be fermented by gut microbiota, but it is unknown how fermentation impacts immune modulating capacity and whether the process of fermentation is dependent on the infant's age. Methods and results The in vitro fermentation of chicory fructo‐oligosaccharides (FOS) and native inulin are investigated using pooled fecal inocula of two‐ and eight‐week‐o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 43 publications
3
33
0
Order By: Relevance
“…The SCFA content of ileal and cecal digesta was determined by gas chromatography (GC-FID), as described by Logtenberg et al (2020) [ 39 ]. An aqueous solution of acetic, butyric, propionic, isobutyric, and isovaleric acids (Sigma-Aldrich) was prepared for quantification.…”
Section: Methodsmentioning
confidence: 99%
“…The SCFA content of ileal and cecal digesta was determined by gas chromatography (GC-FID), as described by Logtenberg et al (2020) [ 39 ]. An aqueous solution of acetic, butyric, propionic, isobutyric, and isovaleric acids (Sigma-Aldrich) was prepared for quantification.…”
Section: Methodsmentioning
confidence: 99%
“…Fibres have been shown to possess immunomodulatory properties (80) ; in the case of infant gut microbiota, the prebiotic inulin has been observed, in vitro, to attenuate pro-inflammatory responses (81) , whilst Vogt et al (82) found that inulin supplementation along with hepatitis B vaccination led to higher in vitro antibody titres compared with control intervention. Research by Trompette et al (83) showed that high fibre levels in the diet of mice influenced the gut microbiota and SCFA levels.…”
Section: Aspects Of Gut Microbiota Modulation Related To Respiratory Infection and Covid-19mentioning
confidence: 99%
“…The degradation of native inulin and 2'-FL by infant fecal microbiota was monitored by high performance anion exchange chromatography (HPAEC) using a CarboPac PA-1 column (250 mm x 2 mm ID) (Dionex, Sunnyvale, CA, USA) and a CarboPac PA guard Please do not adjust margins Please do not adjust margins column (25 mm x 2 mm ID) (Dionex) as described elsewhere with minor modification of the eluent profile. 6 Mobile phase A (0.1 M sodium hydroxide) and B (1 M sodium acetate in 0.1 m sodium hydroxide) were eluted as follows: 0-40 min, 0-40% B; 40-45 min, 40-100% B; 45-50 min, washing step with 100% B; 50-51 min, 100-0% B; 51-66 min, equilibration with 100% A.…”
Section: Fate Of Native Inulin and 2'-fl During Fermentationmentioning
confidence: 99%
“…The application of new combinations of NDCs and HMOs can be of interest to tailor infant formulas for specific groups of infants as it was shown that NDCs and HMOs all have their own unique structureand infant-age-dependent immune effects. [6][7][8] Inulin-type fructans can be found in many natural sources including beet roots, leeks and banana, but is mainly extracted from chicory roots. They are composed of linear chains of (2-1)-linked fructose monomers and either have a glucose or a fructose moiety at the reducing end, 3 with chains with a varying degree of polymerization (DP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation